Rocks and minerals; a guide to familiar minerals, gems, ores, and rocks - Zim, Herbert S. (Herbert Spencer), 1909-1994.; Shaffer, Paul R. (Paul Raymond), 1910-; Perlman, Raymond (New York, Golden Press, 1961)
Includes information on collecting and identifying minerals, and sections on metallic, nonmetallic, gem and rock-forming minerals, and on igneous, sedimentary and metamorphic rocks.
Keywords: Mineralogy; Petrology; Mineralogy; Petrology